Behavior of suspending and wetting agents in aqueous environment - Dhawale, Shashikant C; Wadodkar, Sudhir G; Dorle, Avinash K (Asian Journal of Pharmaceutics (AJP), 2014)
This work describes the changes in viscosity, conductivity, pH, electrical conductivity, dielectric constant, zeta potential, UV, and IR spectra of aqueous solutions/dispersions of sodium carboxy methyl cellulose (CMC), Tween 80, and sodium lauryl sulphate (SLS) during aging at different temperatures. Significant reduction in viscosity ofh sodium CMC occurred during aging studies, while relatively small decrease in viscosity was seen with Tween 80 and SLS. Increment in specific conductivity was seen with aging of excipients. Significant increase of zeta potential was also seen with aging of samples. Concomitant shift in IR spectra of samples was observed with aging at 40Â°C.